Why are low-educated adults underrepresented in adult education? Studying the role of educational background in expressing learning needs and barriers. Issue 1 (2nd January 2022) - Van Nieuwenhove, Lisse; De Wever, Bram
ABSTRACT: The shift to a knowledge society has transformed the way we live and work, which is especially challenging to adults with low education levels. Adult education could be the answer, but low-educated adults participate least in adult education. The present study uses data from the Programme for the International Assessment of Adult Competencies to investigate participation needs and barriers of low-, medium- and high-educated adults across 15 European countries (N = 20, 593). Descriptives show that low-educated adults report the lowest need for training to exercise their job and indicate to be the least prevented from taking more training because of experienced barriers. We then analysed which barriers non-participating and participating adults were referring to. While medium- and high-educated non-participants indicate being prevented because of work and family responsibilities, low-educated non-participants chose family responsibilities but mainly and remarkably the option 'other' as their most important barrier. Contrary to medium- and high-educated adults, low-educated adults' most important barrier could not be defined. A possible explanation is that they experience more dispositional barriers (such as bad memories of education or low self-esteem), which were not included in the list. Our results point to the importance of targeting low-educated adults in participation research.